2008
DOI: 10.1590/s0104-11692008000500002
|View full text |Cite
|
Sign up to set email alerts
|

Factors derived from the intrahospitable laboratories that cause stress in infirmary students

Abstract: FACTORES DERIVADOS DE LOS LABORATORIOS INTRAHOSPITALARIOS QUE PROVOCAN ESTRÉS EN LOS ESTUDIANTES DE ENFERMERÍA FATORES DERIVADOS DOS LABORATÓRIOS INTRA-HOSPITALARES QUE PROVOCAM ESTRESSE NOS ESTUDANTES DE ENFERMAGEM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In such care, there is an increasingly large group of patients to take care of and have responsibility for, and nurses often encounter multidiseased and dying patients (Betony 2012). However, previously identified clinical sources of stresssuch as lack of knowledge and professional ability, lack of familiarity with history and medical terms, heavy workload, being in an unfamiliar situation, mistakes with patients or handling of technical instruments (Sheu et al 2002, Basso Musso et al 2008, Chan et al 2009, Jimenez et al 2010 Figure 1 The tree diagram for experience of stress in nursing students (n = 185). be more frequent in hospital settings.…”
Section: Discussionmentioning
confidence: 99%
“…In such care, there is an increasingly large group of patients to take care of and have responsibility for, and nurses often encounter multidiseased and dying patients (Betony 2012). However, previously identified clinical sources of stresssuch as lack of knowledge and professional ability, lack of familiarity with history and medical terms, heavy workload, being in an unfamiliar situation, mistakes with patients or handling of technical instruments (Sheu et al 2002, Basso Musso et al 2008, Chan et al 2009, Jimenez et al 2010 Figure 1 The tree diagram for experience of stress in nursing students (n = 185). be more frequent in hospital settings.…”
Section: Discussionmentioning
confidence: 99%
“…In an academic context, students may regard examination periods, the transition from high school to college, and tasks outside their class requirements as stressors [5]. In a study of nursing students in São Paulo, the most highly rated stressors were found to be making mistakes at work, harming patients, and receiving contradictory instructions [6]. Stress occurs when internal or external sources produce a situation that is interpreted as exceeding a person’s adaptive resources, and this has possible repercussions on the physical and mental health of college students [7].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is defined, for the university environment, as a set of reactions that occurs when the curricular requirements exceed the capabilities or adaptive resources of the student. [6] Moreover, the stress occurrence is secondary to cognitive assessment, i.e., the individual interprets the situations coming from the internal or external environment in different evaluative categories and defines them as a threat, a challenge or not relevant. [7] When they are defined as a threat or as a challenge, the stress and its consequences to life and health of the college students are possible.…”
Section: Introductionmentioning
confidence: 99%